2020
DOI: 10.31557/apjcp.2020.21.11.3267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of BRAF, NRAS, and TERT Promoter Mutation in Preoperative Thyroid Fine-Needle Aspiration Biopsy: A Diagnostic Study From Dharmais Cancer Hospital

Abstract: Objective: Molecular testing of thyroid nodules becomes important for improving the accuracy of fine-needle aspiration biopsy (FNAB). This study aimed to investigate the diagnostic utility of BRAF, NRAS, and TERT promoter mutation in thyroid nodules at Dharmais Cancer Hospital. Methods: We performed a prospective diagnostic study involving 50 patients with thyroid nodules who needed surgery between September 2013 and August 2014. Mutational hotspots in BRAF exon 15, NRAS exon 3, and TERT promoter region were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“… 36 , 37 The prevalence of BRAF V600E mutation in PTC is 63.6%–83% among Korean and Chinese PTC patients, 38 , 39 , 40 which is much higher than that reported in Western countries (30–72%). 41 , 42 In our study, the frequency of BRAF V600E mutation in PTC was 76.1%. The different prevalence of BRAF V600E mutations among populations may be related to variations in iodine consumption in the diet.…”
Section: Discussionsupporting
confidence: 44%
“… 36 , 37 The prevalence of BRAF V600E mutation in PTC is 63.6%–83% among Korean and Chinese PTC patients, 38 , 39 , 40 which is much higher than that reported in Western countries (30–72%). 41 , 42 In our study, the frequency of BRAF V600E mutation in PTC was 76.1%. The different prevalence of BRAF V600E mutations among populations may be related to variations in iodine consumption in the diet.…”
Section: Discussionsupporting
confidence: 44%
“…This result is similar to the previous finding from Southeast Asia by Navarro-Locsin et al, 22 which reported the BRAFV600E mutation rate was 38.5%. Similar to our result, there were studies in Indonesia conducted by Heriyanto et al 23 and Perdana AB et al 18 that used molecular methods and reported BRAFV600E mutation rates were 40.3% and 31%, respectively. A single-center cohort study in Singapore reported BRAF mutation in 56% of the PTC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Yet, most of the studies used immunohistochemistry modality and/or cytology specimens with limited samples. [14][15][16][17][18] Given the dearth of research describing the prevalence of BRAF and RAS mutations in PTC in Indonesia, this study aimed to assess the prevalence of BRAFV600E, BRAFK601E, and RAS (NRAS, HRAS, and KRAS) mutations and their association with the clinicopathological profiles of PTC that were related to the tumor behavior and prognosis in Indonesian population.…”
Section: Introductionmentioning
confidence: 99%
“…Although most thyroid nodules can be accurately identified as benign or malignant, 10%-40% of thyroid nodules are unable to be identified by FNA biopsy [5,6,22,23]. In our previous study, there were 30% of indeterminate results with most of them confirmed histopathologically to be malignant [24]. This means that up to 3 out of 10 patients may have cancer that is not precisely diagnosed, which confirms the high rate of underdiagnosed cases from FNA cytological examination.…”
Section: Discussionmentioning
confidence: 81%